An efficient Pd–NHC catalyst system in situ generated from Na2PdCl4 and PEG-functionalized imidazolium salts for Mizoroki–Heck reactions in water - Sun, Nan; Chen, Meng; Jin, Liqun; Zhao, Wei; Hu, Baoxiang; Shen, Zhenlu; Hu, Xinquan (Beilstein Journal of Organic Chemistry, 2017)
Three PEG-functionalized imidazolium salts L1–L3 were designed and prepared from commercially available materials via a simple method. Their corresponding water soluble Pd–NHC catalysts, in situ generated from the imidazolium salts L1–L3 and Na2PdCl4 in water, showed impressive catalytic activity for aqueous Mizoroki–Heck reactions. The kinetic study revealed that the Pd catalyst derived from the imidazolium salt L1, bearing a pyridine-2-methyl substituent at the N3 atom of the imidazole ring, showed the best catalytic activity. Under the optimal conditions, a wide range of substituted alkenes were achieved in good to excellent yields from various aryl bromides and alkenes with the catalyst TON of up to 10,000.
Keywords: aqueous homogeneous catalysis; Mizoroki–Heck reaction; Na2PdCl4; PEG-functionalized imidazolium salts